Acquisition of Personal Assets Through Loan Bank and Commercial Credit: What’s the Best Option? - Arturo, García-Santillán; Andrea, Ortigosa-Ortiz Alexa; Luz, Hernández-Pérez Sandra; Noelia, Mora-Montalvo; Josefina, Ramos-Hernández Jésica (Quarterly Journal of Econometrics Research, 2016)
The aim of this paper is to determine the most viable and beneficial scenario for acquire an asset, specifically a car. For this purpose, the amortizations model was used, which is why the corresponding financial simulation in the amortization charts on both scenarios are presented. The results lead us to think that the financing option offered by the car company is the most suitable and beneficial for the client.